2022
DOI: 10.1002/cre2.611
|View full text |Cite
|
Sign up to set email alerts
|

The use of silver diamine fluoride in a children's hospital: Critical analysis and action protocol

Abstract: Objectives The present critical analysis aims to propose an action protocol for the use of silver diamine fluoride (SDF) in pediatric patients in a hospital setting, especially for those who are currently awaiting hospital dental treatment under general anesthesia. Material and Methods A literature search was performed in the PubMed/MEDLINE from 2009 to 2021 using the search terms “silver diamine fluoride”, “pediatrics silver diamine fluoride”, “application silver diamine fluoride”, and “AND” ‐ combined with t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 57 publications
0
0
0
Order By: Relevance
“…Another factor to consider is the higher utilization of GA in Spain compared to Italy. This result is consistent with the study by Brunet et al (24), which reports that approximately 10% of paediatric patients attending the Department of Paediatric Dentistry at the Sant Joan de Déu Hospital in Barcelona annually receive dental treatments under GA. Moreover, Guinot et al (25) and Veloso et al (26) observed that despite being the least favored technique, GA is generally an accepted mode of treatment delivery in Spain.…”
Section: Discussionsupporting
confidence: 93%
“…Another factor to consider is the higher utilization of GA in Spain compared to Italy. This result is consistent with the study by Brunet et al (24), which reports that approximately 10% of paediatric patients attending the Department of Paediatric Dentistry at the Sant Joan de Déu Hospital in Barcelona annually receive dental treatments under GA. Moreover, Guinot et al (25) and Veloso et al (26) observed that despite being the least favored technique, GA is generally an accepted mode of treatment delivery in Spain.…”
Section: Discussionsupporting
confidence: 93%